Resiliensi Pada Pekerja Perempua - Fitri Ramadhani; Nina Zulida Situmorang; Ciptasari Prabawanti (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
Resilience is an ability of self-resilience that every individual must have in living his life so that individuals are able to organize their lives well. The purpose of this study was to determine the resilience of female workers during the pandemic in Yogyakarta and the aspects affecting the resilience of female workers during the pandemic in Yogyakarta. This research is a qualitative type with a phenomenological approach through the interview method with six informants. The results showed that women during the pandemic had good resilience by avoiding negative thoughts and trying to be individuals who built a positive life with family support as the first bastion so that informants maintain their spiritual and physical health. This triggered the informants to remain productive in order to build a happy and healthy family environment.